Carbon Monoxide Off-Gassing From Bags of Wood Pellets. Issue 2 (25th December 2017) - Rahman, Mohammad Arifur; Rossner, Alan; Hopke, Philip K
Abstract: Wood pellets are increasingly used for space heating in the United States and globally. Prior work has shown that stored bulk wood pellets produce sufficient carbon monoxide (CO) to represent a health concern and exceed regulatory standards for occupational exposures. However, most of the pellets used for residential heating are sold in 40-pound (18.1 kg) plastic bags. This study measured CO emission factors from fresh, bagged-wood pellets as a function of temperature and relative humidity. CO concentrations increased with increasing temperature and moisture in the container. CO measurements in a pellet mill warehouse with stored pallets of bagged pellets had 8-h average CO concentrations up to 100 ppm exceeding occupational standards for worker exposure. Thus, manufacturers, distributors, and home owners should be aware of the potential for CO in storage areas and design facilities with appropriate ventilation and CO sensors.